2017
DOI: 10.1371/journal.pone.0171390
|View full text |Cite
|
Sign up to set email alerts
|

Differential and directional estrogenic signaling pathways induced by enterolignans and their precursors

Abstract: Mammalian lignans or enterolignans are metabolites of plant lignans, an important category of phytochemicals. Although they are known to be associated with estrogenic activity, cell signaling pathways leading to specific cell functions, and especially the differences among lignans, have not been explored. We examined the estrogenic activity of enterolignans and their precursor plant lignans and cell signaling pathways for some cell functions, cell cycle and chemokine secretion. We used DNA microarray-based gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 46 publications
(58 reference statements)
1
31
0
Order By: Relevance
“…Control cells were exposed to the same vehicle of cells treated with E2 (0.1% etanol) or antagonist (0.1% DMSO). All concentrations and times selected were chosen taking into account previous studies [5,19,20]. A schematic workflow of the experimental design is provided in Fig.…”
Section: Cell Culture and Experimental Designmentioning
confidence: 99%
“…Control cells were exposed to the same vehicle of cells treated with E2 (0.1% etanol) or antagonist (0.1% DMSO). All concentrations and times selected were chosen taking into account previous studies [5,19,20]. A schematic workflow of the experimental design is provided in Fig.…”
Section: Cell Culture and Experimental Designmentioning
confidence: 99%
“…Our finding of a stronger correlation with enterolactone than enterodiol may be explained by the shorter half-life of enterodiol, which is further metabolized into enterolactone (7,8). Additionally, in vitro and in vivo studies have demonstrated differential effects of enterolactone and enterodiol on estrogenrelated pathways in cancer development (54)(55)(56).…”
Section: Discussionmentioning
confidence: 74%
“…Over the decades, many studies have supported the estrobolome hypothesis ( Figure 2) [12][13][14][15][16]19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Germfree rats excrete unquantifiable amounts of hormones whereas conventional rats, under the same conditions, excrete significant amount of free steroid hormones measurable by gas chromatography and mass spectrometry [33].…”
Section: An Active Estrobolome Regulates Estrogen Levelsmentioning
confidence: 99%
“…In addition to metabolizing estrogens, enteric microbes perform a very important role in synthesis of estrogen-like compounds or estrogen mimics from dietary sources [27,32,[48][49][50][51][52]. Phytoestrogens are group of plant compounds containing one to two benzene ring and two or three hydroxyl groups, similar to 17β-estradiol in structure and molecular weight [53].…”
Section: Enteric Microbes and Phytoestrogensmentioning
confidence: 99%
See 1 more Smart Citation